Assessing Indonesia-Russia Foreign Policy During Susilo Bambang Yudhoyono Administration - Marten Hanura (Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Russia or formerly known as the Soviet Union has a historically unique cooperation and diplomatic relations with Indonesia. This is because the relationship between Indonesia and Russia has a long history and experiencing ups and downs. The closeness of the two countries was influenced ideologically in the early days of Indonesian independence, and later the rise of the New Order regime influenced the dynamics of Indonesian foreign policy. During the New Order period, the Indonesian government began to freeze all forms of cooperative relations with the Soviet Union. The collapse of the Soviet Union and the end of the Cold War era began to change the map of international politics to affect the situation in Indonesia. In the Post-Reformation era, the normalization of relations between the two countries recovered and lasted until the administration of President Susilo Bambang Yudhoyono. The purpose of this article is to find out how the changes in the implementation of the foreign policy of Indonesia-Russia during the administration of President Susilo Bambang Yudhoyono with the previous era and what factors underlie Indonesia's foreign policy towards Russia. This research uses the descriptive-analytical method and using some theoretical concepts in the foreign policy-making process. The results of this study concluded that foreign policy between Indonesia and Russia increased significantly in the Post-Reformation era which no longer saw Russia as a threat as in the New Order era. The cooperation between Indonesia and Russia is implemented in various main areas, prominently is the cooperation in the field of military, social, economic and political.